Profile of End Stage Chronic Kidney Disease due to Obstructive Uropathy Patients Undergoing Hemodialysis (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2024)
Introduction. Chronic Kidney Disease (CKD) is a condition of gradual decline in kidney function and ability caused by various kidney diseases. CKD can be caused by several conditions, including obstructive uropathy. Hemodialysis is one of the therapy options for CKD patients. The purpose of this study was to analyze the profile of CKD due to obstructive uropathy patients at Saiful Anwar General Hospital Malang, who underwent hemodialysis. Methods. This study is a descriptive observational research with a cross sectional design, which uses secondary data taken from medical records of patients with end-stage CKD due to obstructive uropathy who undergo hemodialysis in the hemodialysis unit of Dr. Saiful Anwar General Hospital Malang, for the period of 2021-2023. Result. Based on the gender, there were more male patients than female patients (53.13%:46.87%) were females. Hypertension comorbidity was the highest percentage, 71.88%. Based on various conditions, urinary tract stones were the highest cause of obstructive uropathy compared to other causes with a percentage of 62.5%. Conclusion. The result showed that patients were predominantly male with comorbid hypertension. The most common cause of obstructive uropathy in this study was urinary tract stones. Keywords: chronic kidney disease, hemodialysis, obstructive uropathy